Penerapan Model Role Playing Untuk Meningkatkan Keaktifan dan Hasil Belajar Siswa Pada Mata Pelajaran Pkn Kelas III SD IT Darussalam Bayan - Wijokongko, Tabah; Khaq, Muflikhul; Anjarini, Titi (Program Studi Pendidikan Guru Madrasah Ibtidaiyyah (PGMI) IAINU Kebeumen, 2023)
This study used classroom action research (CAR) which consists ofa cycle. Each cycle consists of two meetings. The subjects in this study were grade III students of SD IT Darussalam Bayan totaling 17 students, the data collection methods used were interviews, observations, and documentation. With the following role playing steps: 1) warm up the atmosphere and motivate students, 2) choose roles, 3) arrange role stages, 4) prepare observations, 5) cast, 6) discussion and evaluation, 7) share experiences and draw conclusions. Based on research analysis data that has been conducted using role playing models about student activeness getting an average in the precycle 60%, then in cycle I 67.64% and cycle II 80.39%, it can be concluded that the application of role playing models can increase student activeness, while the results Student learning with the application of role playing at the pre-cycle stage gets an average of 60, cycle I 70.83 and cycle II 80.88 thus it can be concluded that the role playing model can improve student learning outcomes.